1973
DOI: 10.1098/rspa.1973.0064
|View full text |Cite
|
Sign up to set email alerts
|

On the transport of compact particles through solutions of chain-polymers

Abstract: The problem is discussed of providing a theoretical explanation for the empirical equation of Laurent, Bjork, Pietruszkiewicz & Persson (1963) which relates the relative retardation of the sedimentation of compact particles in solutions of hyaluronic acid to the radius of the particle and the concentration of hyaluronic acid. From published and original data, the same relation is shown to apply also to sedimentation and diffusion in solutions of a number of linear and branched chain-polymers. Of several ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
185
0
3

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(199 citation statements)
references
References 25 publications
11
185
0
3
Order By: Relevance
“…They may be correlated with the size of the solutes using theories that describe hindered diffusion of macromolecules in nonadsorbing hydrogels (Kim and Chauhan, 2008;Ogston et al, 1973;Phillips, 2000;Saini et al, 2005;Tomic et al, 2007). Based on the assumption of Brady (Clague and Phillips, 1996) that the relative diffusivity, defined as the ratio between the diffusion coefficients in the gel and in the dilute, bulk solution, is given by < = " • -, where F is a hydrodynamic-resistance factor and S is a steric factor, several diffusion models that have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They may be correlated with the size of the solutes using theories that describe hindered diffusion of macromolecules in nonadsorbing hydrogels (Kim and Chauhan, 2008;Ogston et al, 1973;Phillips, 2000;Saini et al, 2005;Tomic et al, 2007). Based on the assumption of Brady (Clague and Phillips, 1996) that the relative diffusivity, defined as the ratio between the diffusion coefficients in the gel and in the dilute, bulk solution, is given by < = " • -, where F is a hydrodynamic-resistance factor and S is a steric factor, several diffusion models that have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the assumption of Brady (Clague and Phillips, 1996) that the relative diffusivity, defined as the ratio between the diffusion coefficients in the gel and in the dilute, bulk solution, is given by < = " • -, where F is a hydrodynamic-resistance factor and S is a steric factor, several diffusion models that have been proposed. In the simplest approach of Ogston et al (Ogston et al, 1973), the hydrodynamic-resistance is neglected (F = 1), and the relative diffusivity is given by:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single microchannel was assumed to be representative of the entire channel array, since chemoattractant diffusion between neighboring channels can only occur at their endpoints. The relevant chemoatttractant, CCL21, is predicted to have a diffusion constant of 1.0•10 -10 m 2 /s in pure water, which may be reduced by a factor of 2-3 when diffusing in aqueous polymer networks (Ogston et al 1973;Wang and Irvine 2013). Previous interaction studies did not show any binding of CCL21 to fibrillar collagen I (Haessler et al 2011;Wang and Irvine 2013), which greatly simplifies the numerical modeling.…”
Section: Finite Element Modelingmentioning
confidence: 95%
“…The friction exerted by the polymer network was thus low but the steric hindrance for translational movements was high. I n an interesting treatment by Ogston et al [6] it was shown that experimental data on the retardation of the translational movements of particles in polymer solutions [3 -61 can be quantitatively described to be a function of the probability that a free space will occur in the neighbourhood of a particle into which it can move. These authors' description of translational diffusion thus agrees with the view reached from our studies on rotational diffusion.…”
mentioning
confidence: 99%